Determination of Climatic Impact of Temperature in Presence of Avian Respiratory Infections in Villa Clara Province, Cuba - Rigoberto Fimia Duarte; Ricardo Osés Rodríguez; David del Valle Laveaga; María Patricia Zambrano Gavilanes; Pedro Yoelvys de la Fé Rodríguez; Yanira Zaita Ferrer; Fran M. Wilford González; Ismabel Domínguez Hurtado (New Frontiers in Medicine and Medical Research Vol. 16, 2021)
The objective of the research was to determine the climatic impact of temperature on avian respiratory infections in Villa Clara province, Cuba. In this work retrospective data were used to obtain the epizootiological statistical information of susceptible and dead birds regarding avian respiratory infections, in specialized poultry farms of Villa Clara province, during the period 2005-2007. These data were correlated with the temperatures stockings average corresponding to this period in this county. The total of deaths was correlated with the total of susceptible; these last ones correlated in turn with the provincial temperatures stockings. For the information processing, the model Autoregressive Integrated Moving Averages (ARIMA) was used of Box-Jenkins Methodology through the statistical package SPSS Version 13. Techniques of multivariate regression for modeling the total of poultry deaths were also applied. The final ARIMA model expressed that an increase of 1 degree of temperature, which meant an increase of 53.37 deaths. It was also used a 95% of probability value. This work allows corroborating and quantifying the impact of mean temperature in the susceptible and in the poultry deaths in the study area of Villa Clara province, Cuba. It was obtained that with 1ºC of monthly half temperature, it can be expected an increase of 8 894 susceptible cases and as the susceptible ones’ increase in 1000 the deaths, are increased in 6 birds, for what the susceptible ones for 0.06 will be the same approximately to the total of deaths.